I'll give you a further hint. The "associated homogeneous equation" is f''- f= 0. If you try a solution of the form f(x)= e^(ax) then f'= ae^(ax) and f''= a^2e^(ax) so the equation becomes f''- f= a^2e^(ax)- e^(ax)= e^(ax)(a^2- 1)= 0. e^(ax) is never 0 so what must a equal?
So what is the general solution to the associated homogeneous equation?
What do you get if you also try f(x)= Axe^x where A is a constant?
Now, I suspect that, if you have been given a problem like this, you must be taking an introductory course in "Differential Equations".
So why don't you already know all this?